Optical and molecular diversity of dissolved organic matter in sediments of the Daning and Shennong tributaries of the Three Gorges Reservoir - Wang, Kai; Fang, Hongwei; He, Guojian; Huang, Lei; Cui, Zhenghui; Gao, Qifeng; Xu, Song; Wang, Dianchang; Wu, Xinghua; He, Ding (Frontiers in Environmental Science, 2023)
Damming significantly modified the function of natural river networks and influenced sediment dynamics with reservoir operation. The dissolved organic matter (DOM) in sediment of reservoirs involves severely in carbon flow from land to sea. However, the property of DOM (e.g., quantity and quality) in sediment of reservoirs, and their relationship with the carbon cycle, remain unclear for the complex reservoir construction interrupted environmental processes. In this work, we characterize the optical and molecular properties of sediment water-extractable organic matter (WEOM) in Daning and Shennong tributaries of the world's largest reservoir (Three Gorges Reservoir, TGR) with the application of optical techniques and ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). Firstly, the linkage between light-absorbing components and individual molecule of WEOM was assessed, which presented a significant difference to DOM in water and indicated that there might be an intrinsic variation between DOM in sediment and water. Then with the unique optical-molecular property linkage assessed, multiple sources (autochthonous and terrestrial sources) were identified, and a declining trend of terrestrial and recalcitrant WEOM was revealed from tributary upstream to downstream. Finally, combining with the covariance analysis of property between WEOM and sediment particle, we demonstrated that the WEOM dynamic was likely regulated by hydrologic sorting induced particle size and mineral composition variations of sediment. Moreover, assessment between lability and WEOM molecular property suggested that WEOM dynamic likely contributed to carbon burial of reservoir. Therefore, the study emphasizes the influence of dam construction on organic matter accumulation and riverine carbon cycling.